Effect of Neonatal Phototherapy on Eosinophil Levels in Nonsevere Hyperbilirubinemia - Can, Ceren; Hamilcıkan, Şahin (American Journal of Perinatology, 2020)
Objective The purpose of the research was to determine the impact of phototherapy (PT) on eosinophil levels in neonates with nonsevere bilirubin levels (<20 mg/dL) treated with PT.Study Design This observational pilot study included term neonates with early neonatal hyperbilirubinemia.Results Ninety-six term neonates were included in the study. The male-to-female ratio was 1.23. Hyperbilirubinemia was most frequently related to ABO group incompatibility (49%). Fifty-two neonates (54.1%) were born by normal spontaneous delivery. After PT, while total serum bilirubin, hemoglobin, hematocrit, leukocyte, and neutrophil levels were found to be significantly decreased, eosinophil levels were significantly increased (p = 0.01). No significant difference was found regarding lymphocyte and basophil levels after PT. A statistically significant correlation was found between bilirubin and eosinophil levels before PT (r2 = 0.28, p = 0.03). No correlation between eosinophil levels and treatment age, gender, diagnosis of hyperbilirubinemia, and delivery route before PT was found. After PT, eosinophil levels increased, while other blood cell series were found to be decreased. The correlation between the bilirubin levels and eosinophil was found to be negative (r2 = − 0.32, p = 0.02) after PT.Conclusion PT may increase serum eosinophil levels in term neonates with nonsevere hyperbilirubinemia.
Keywords: hyperbilirubinemia; eosinophils; phototherapy; newborn